The Effect of Teaching in the English Language on the Understanding of Biological Concepts Among the Students of the Second Intermediate Grade in the Distinguished Schools - Hasan Mesto, Hashim (JOM, 2023)
In view of the importance of the English language in teaching and the specificity of scientific subjects as it is the language of science and communication and the language of modern scientific technologies in the world, and in line with these data, the decision of the Ministry of Education in the Republic of Iraq was to instruct the teaching of scientific subjects (Mathematics, Physics, Chemistry, Biology) in the schools of gifted and distinguished students by the language English and according to the curricula prepared for that. Today, despite the passage of six years since the application of this experiment began, there is no scientific study (as far as the researcher knows) based on this experiment from a scientific point of view in terms of results, except for poor discussions on the margins between supporters and opponents of the teachers in charge of teaching these subjects. The sources of these attitudes are multiplied between a national standpoint to preserve identity or an objective one since language is an essential part of the structure of thinking, and therefore teaching science in a language other than the mother tongue negatively affects the efficiency of understanding and assimilation of various scientific concepts to varying degrees according to the nature of the study material. The researcher, through his teaching of life sciences for intermediate stages, was an eyewitness to the problems that students suffer from during their studies, and from this point of view, it was necessary to try to conduct a scientific evaluation on the results of this experiment in an attempt to overcome ready-made judgments, whether supporters or opponents that are not based on objective data, thus placing the decision maker on a clear awareness in the process of evaluating the experiment.